Genome-wide meta-analysis of brain volume identifies genomic loci and genes shared with intelligence - Philip R. Jansen (Nature Portfolio, 2020)
Brain volume and intelligence have been previously found to have shared genetic etiology, but the specific common genetic signals have not been identified. Here, the authors perform a genome-wide association study on brain volume, finding common genetic loci driving brain volume and intelligence.